Segnico, simbolico, politico: Note sulla teoria della significazione di Ernesto Laclau e Chantal Mouffe (Materiali di Estetica. Terza serie, 2022)
This article explores some central features of the theory of signification put forward by Ernesto Laclau and Chantal Mouffe, taking into account both Hegemony and Socialist Strategy and some further reflections developed by Laclau alone. Through the analysis of the concepts of discourse, empty signifier, dislocation and antagonism it is argued that, in the discourse-theoretical framework, the Saussurean “arbitrariness of the sign” can be limited only through the symbolic unification of a discourse and the drawing of antagonistic frontiers, and that these latter processes rest on contingent decisions, that is operations pertaining to the order of the political.
Keywords: Laclau and Mouffe; Discourse; Empty signifier; Symbol; the Political